Peran Media Informasi pada Usahatani Padi Sawah di Kelurahan Galung Kecamatan Liliriaja Kabupaten Soppeng - Sumange, Andi Muhammad Faried Anshari; Sumange, La; Rahman, Syamsul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Increasing food security today is not only a real action in agricultural activities, but has implemented information technology for data processing, and has been used in various fields, especially agriculture based on the internet and multimedia, especially millennial farmers in utilizing technology to increase their farming productivity. The study was conducted from February to April 2025 in Galung Village. The farmer population was 153 people, 15% were selected so that 23 people were selected as samples. The study aims to examine social media and supporting and inhibiting factors for the use of social media in Rice Farming in Galung Village. Data analysis used is descriptive and analysis using the Likert Scale. The results of the study showed that the use of social media Youtube and WhatsApp for hand tractors had a very influential value of 3.7 and 3.6, Transplanters via Youtube, Facebook and WhatsApp had an influence, quite influential with values 2.5, 1.5 and 1.8. Combine Harvester had an influence, quite influential, values 2.8, 2.4 and 1.3. Technology in the form of seeds, fertilizers and medicines had